Tropomodulin isoforms utilize specific binding functions to modulate dendrite development. Issue 6 (8th June 2016) - Gray, Kevin T.; Suchowerska, Alexandra K.; Bland, Tyler; Colpan, Mert; Wayman, Gary; Fath, Thomas; Kostyukova, Alla S.
Abstract : Tropomodulins (Tmods) cap F‐actin pointed ends and have altered expression in the brain in neurological diseases. The function of Tmods in neurons has been poorly studied and their role in neurological diseases is entirely unknown. In this article, we show that Tmod1 and Tmod2, but not Tmod3, are positive regulators of dendritic complexity and dendritic spine morphology. Tmod1 increases dendritic branching distal from the cell body and the number of filopodia/thin spines. Tmod2 increases dendritic branching proximal to the cell body and the number of mature dendritic spines. Tmods utilize two actin‐binding sites and two tropomyosin (Tpm)‐binding sites to cap F‐actin. Overexpression of Tmods with disrupted Tpm‐binding sites indicates that Tmod1 and Tmod2 differentially utilize their Tpm‐ and actin‐binding sites to affect morphology. Disruption of Tmod1's Tpm‐binding sites abolished the overexpression phenotype. In contrast, overexpression of the mutated Tmod2 caused the same phenotype as wild type overexpression. Proximity ligation assays indicate that the mutated Tmods are shuttled similarly to wild type Tmods. Our data begins to uncover the roles of Tmods in neural development and the mechanism by which Tmods alter neural morphology. These observations in combination with altered Tmod expression found in several neurological diseases also suggest that dysregulation of Tmod expression may be involved in the pathology of these diseases. © 2016 Wiley Periodicals, Inc.